Implementasi pendidikan karakter melalui kurikulum merdeka belajar di sekolah dasar - Rahmah, Fitri Aulia (Maliki Interdisciplinary Journal, 2025)
Character education is one of the top priorities in human resource development in Indonesia. The Merdeka Belajar Curriculum provides wider opportunities for student character development through a contextual, flexible, and needs-based approach. This article discusses the implementation of character education in Merdeka Belajar Curriculum in elementary schools, including its definition, objectives, and implementation forms. Based on the study, the main strategies include thematic approaches, integration of values in learning, and extracurricular programs. This research uses a qualitative method with data collection techniques in the form of literature review. In practice, this character education also presents significant challenges, such as limited human resources and adequate facility support. Therefore, collaboration between the school, parents and the community is needed to achieve optimal results.